Development of a porous poly(DL-lactic acid-co-glycolic acid)-based scaffold for mastoid air-cell regeneration - Gould, Toby W.A.; Birchall, John P.; Mallick, Ali S.; Alliston, Tamara; Lustig, Lawrence R.; Shakesheff, Kevin M.; Rahman, Cheryl V. (Wiley, 2013)
Objectives/Hypothesis: To develop a porous, biodegradable scaffold for mastoid air-cell regeneration. Study Design: In vitro development of a temperature-sensitive poly(DL-lactic acid-co-glycolic acid)/poly(ethylene glycol) (PLGA/PEG) scaffold tailored for this application. Methods: Human mastoid bone microstructure and porosity were investigated using micro-computed tomography. PLGA/PEG-alginate scaffolds were developed, and scaffold porosity was assessed. Human bone marrow mesenchymal stem cells (hBM-MSCs) were cultured on the scaffolds in vitro. Scaffolds were loaded with ciprofloxacin, and release of ciprofloxacin over time in vitro was assessed. Results: Porosity of human mastoid bone was measured at 83% with an average pore size of 1.3 mm. PLGA/PEG-alginate scaffold porosity ranged from 43% to 78% depending on the alginate bead content. The hBM-MSCs proliferate on the scaffolds in vitro, and release of ciprofloxacin from the scaffolds was demonstrated over 7 to 10 weeks. Conclusions: The PLGA/PEG-alginate scaffolds developed in this study demonstrate similar structural features to human mastoid bone, support cell growth, and display sustained antibiotic release. These scaffolds may be of potential clinical use in mastoid air-cell regeneration. Further in vivo studies to assess the suitability of PLGA/PEG-alginate scaffolds for this application are required. Key Words: Scaffold, poly(DL-lactic acid-co-glycolic acid), alginate, mastoid, ciprofloxacin. Level of Evidence: N/A.